Cardiovascular risk factors and 30-year cardiovascular risk in homeless adults with mental illness - Gozdzik, Agnes (BMC Public Health, 2015)
BACKGROUND: Cardiovascular disease (CVD) is a leading cause of death among homeless people. This study examines CVD risk factors and 30-year CVD risk in a population of homeless individuals with mental illness. METHODS: CVD risks factors were assessed in 352 homeless individuals with mental illness in Toronto, Canada, at the time of their enrollment in the At Home/Chez Soi Project, a randomized trial of a Housing First intervention. The 30-year risk for CVD (coronary death, myocardial infarction, and fatal or nonfatal stroke) was calculated using published formulas and examined for association with need for mental health services, diagnosis of psychotic disorder, sex, ethnicity, access to a family physician and diagnosis of substance dependence. RESULTS: The 30-year CVD risk for study participants was 24.5 ± 18.4%, more than double the reference normal of 10.1 ± 7.21% (difference = −13.0% 95% CI −16.5% to −9.48%). Univariate analyses revealed 30-year CVD risk was greater among males (OR 3.99, 95% CI 2.47 to 6.56) and those who were diagnosed with substance dependence at baseline (OR 1.94 95% CI 1.23 to 3.06) and reduced among those who were non-white (OR 0.62 95% CI 0.39 to 0.97). In adjusted analyses, only male sex (OR 4.71 95% CI 2.76 to 8.05) and diagnosis of substance dependence (OR 1.78 95% CI 1.05 to 3.00) remained associated with increased CVD risk. CONCLUSIONS: Homeless people with mental illness have highly elevated 30-year CVD risk, particularly among males and those diagnosed with substance dependence. This study adds to the literature by reporting on CVD risk in a particularly vulnerable population of homeless individuals experiencing mental illness, and by using a 30-year CVD risk calculator which provides a longer time-frame during which the effect of modifiable CVD risk factors could be mitigated. TRIAL REGISTRATION: Current Controlled Trials ISRCTN42520374 ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12889-015-1472-4) contains supplementary material, which is available to authorized users.